(untitled) (Bangladesh Journal of Otorhinolaryngology, 2012)
Internal auditory canal (IAC) stenosis is a rare cause of sensorineural hearing loss. Patient may present with symptoms of progressive facial nerve palsy, hearing loss, tinnitus and giddiness. High resolution temporal bone CT-scan and magnetic resonance imaging (MRI) are the important tools for diagnosis. No specific management has been devised. Here is presentation of a case of unilateral (left) IAC stenosis with profound hearing loss and progressive House Brackmann Grade III-IV facial weakness. The diameter of the IAC was less than 2 mm on high resolution temporal bone computed tomography (HRCT) scan. It was managed by facial nerve decompression by translabyrinthine approach in an attempt to prevent further deterioration of facial palsy. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12014 Bangladesh J Otorhinolaryngol 2012; 18(2): 179-182